First survey of Simuliidae (Diptera) from the North of Ceara State, Brazil, with description of a new species and identification keys for the immature stages - Pessoa, Felipe Arley Costa; Velásquez, Claudia María Ríos; Py-Daniel, Victor (Zootaxa, 2005)
The first survey of black flies (Diptera: Simuliidae) in Ceará State, Brazil, resulted in the discovery of a new species, Inaequalium maranguapense, for which larvae, pupae, and pharate females are described. This new species was found in a small stream in a mountainous region near the coast. The female has a cibarium lacking the typical central elevation of the genus; the pupa has four gill filaments inflated proximally and arising from the same point; the larva has rectal papillae typically comprised of simple lobes. The following additional species were collected from Ceará State: Chirostilbia acarayense, Ectemnaspis perflava, E. nr. kabanayense, Hemicnetha rubrithorax, H. brachyclada, I. subnigrum, and Psaroniocompsa incrustata. The cibarium of E. perflava is redescribed. Identification keys to the larvae and pupae of black flies from the study area are provided.